Peningkatan Kesadaran Sosial, Penguatan SDM, dan Pemberdayaan UMKM melalui Program Kuliah Kerja Nyata di Desa Nagacipta - Ela Fauziah; Ilham Canakia; Ending Sution; Sarika Sarika (Lembaga Pengembangan Kinerja Dosen, 2025)
The Community Service Program (KKN) is a tangible form of student service to the community through the application of knowledge in the field. Nagacipta Village, Serang Baru Subdistrict, Bekasi Regency, was chosen as the location for the KKN because it has considerable potential for community economic development, particularly through the Micro, Small, and Medium Enterprises (MSME) sector, and faces various challenges in the fields of education, social affairs, and culture. The objectives of this activity are to empower the community through education in schools, MSME assistance, and increased social awareness in order to support sustainable village development. The implementation method used is a qualitative descriptive approach with a participatory element (Participatory Action Research/PAR). The stages involved observation, interviews, group discussions with village officials, youth, and the community, work program preparation, implementation, and evaluation. The main programs implemented included anti-bullying and hygiene education in schools, simple digital marketing training for MSMEs, environmental health education, and support for community social and cultural activities. The results showed an increase in students' awareness of hygiene and mutual respect, the development of MSME actors' knowledge of digital promotion through social media, and increased community participation in social and cultural activities. Documentation of the activities also showed the active involvement of the community and the support of village officials. In conclusion, the KKN program in Nagacipta Village made a positive contribution to community empowerment and MSME development. This program is expected to be the first step in strengthening the village's economic independence and improving the quality of human resources. Recommendations are given for similar programs to continue with ongoing support from the village government, educational institutions, and the next KKN period.